Are effects of school resource officers moderated by student race and ethnicity - Crosse, Scott (Crime & delinquency, 2022)
We examined whether effects of an increase in school resource officer (SRO) staffing on school crime and exclusionary disciplinary responses to school crime varied by student race and ethnicity. Using monthly school level administrative data, we compared change in outcomes for 33 schools that enhanced SRO staffing and a matched sample of 72 schools that did not increase SRO staffing at the same time. We found that increases in offenses and exclusionary reactions due to increased SRO presence were most evident for Black and Hispanic as opposed to White students. Educational decision-makers should carefully weigh the benefits of placing SROs in schools against the knowledge that this practice differentially increases recorded school crime and exclusion from school for students of color.